2014 oil plunge: Causes and impacts on renewable energy. (February 2017) - Khan, Muhammad Imran; Yasmeen, Tabassam; Shakoor, Abdul; Khan, Niaz Bahadur; Muhammad, Riaz
Abstract: Following four years of relative stability at around $106 per barrel (bbl), oil prices have declined sharply since June 2014 and are expected to remain low for a considerable period of time. There are multiple factors which are being considered behind the plunge in the price of oil since June 2014. Most observers have conjectured that domestic oil boom in the United States and Iraq is the major cause for the falling oil prices. Some have suggested that a major shock to oil price expectations occurred after the November 2014 meeting of OPEC, when they did not cut production despite the steady increase in non-OPEC oil production. In this paper, first we analyzed the effect of various factors on the oil prices and then we studied impacts of the falling oil prices on non-hydro renewable energy. We compare the recent decline in oil prices with previous episodes up to 1996. We show that the demand and supply formula cannot be implemented to the current oil plunge. The study shows that so far the recent plunge in oil prices has produced no major impact on renewable energy sector. We found that renewable energies, such as solar and wind, are increasingly becoming cost competitive with fossil fuel energy. However the oil price crash could hurt the short-term outlook for certain specific clean energy technologies such as bio-fuel and electric vehicles that do compete with oil-based transportation. While long term low oil prices may threaten renewable energies, climate policies have the potential to act as a counterweight, encouraging long-term, low carbon, investment.